(untitled) (American Journal of Islam and Society, 1994)
There is a view that imperialism, as a historical practice, constitutes a deviation from western civilization and its conception of the universe, and that the adoption of the imperialist solution, which involves exporting problems to the rest of the world and hegemony over other nations, is inconsistent with being a liberal, humane, and enlightened civilizatian that has accepted democracy as philosophy of government, laissez-faire as its economic order, and rationalism and humanism as universal philosophy. It is our contention, however, that these varied philosophies do not stand in contradiction to the imperialist epistemological vision. Rather, there is a close link between these philosophies and the imperialist vision, which will be fully undelstmd once we turn to the epistemological level. In order to be aware of such a link, it has to be recognized that all of these philosophies are secular in nature, in the sense that they do not admit of any philosophical system outside the domain of the materialistic order. In our view, secularism is not a separation between religion and the state, as propagated in both western and Arab writings. Rather, it is the removal of absolute values-epistemological and ethical-from the world such that the entire world-humanity and nature- alike-becomes merely a utilitarian object to be utilized and subjugated. From this standpoint, we can see the structural similarity between the secular epistemological vision and the imperialist epistemological vision. We can also realize that imperialism is no more than the exporting of a secular epistemological and ethical paradigm from the western world, where it first emerged, to the rest of the world ...